2008
DOI: 10.1186/1472-6882-8-64
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of pomegranate rind extracts: enhancement by addition of metal salts and vitamin C

Abstract: Background: Punica granatum L. or pomegranates, have been reported to have antimicrobial activity against a range of Gram positive and negative bacteria. Pomegranate formulations containing ferrous salts have enhanced although short-term, antibacteriophage activities which are rapidly diminished owing to instability of the ferrous combination. The aim of this study was to determine the antimicrobial activities of combinations of pomegranate rind extracts (PRE) with a range of metals salts with the added stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 26 publications
3
59
1
4
Order By: Relevance
“…Similarly, Alzoreky (2009) reported that water methanol extract was thermo stable, since they retained activity after boiling or sterilization. McCarrell et al (2008) also demonstrated antibacterial activity of autoclaved pomegranate peel extract against Staphylococcus aureus and B.subtilis. The antibacterial effect of PPE was further tested by broth dilution assay.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, Alzoreky (2009) reported that water methanol extract was thermo stable, since they retained activity after boiling or sterilization. McCarrell et al (2008) also demonstrated antibacterial activity of autoclaved pomegranate peel extract against Staphylococcus aureus and B.subtilis. The antibacterial effect of PPE was further tested by broth dilution assay.…”
Section: Resultsmentioning
confidence: 98%
“…McCarrell et al [25] reported that Staphylococcusaureus and Ps. aeroginosa have the highest sensitivities to the aqueous extract of pomegranate peel.…”
Section: Discussionmentioning
confidence: 99%
“…Food-borne illnesses are still an important concern for both consumers, the food industry and food safety authorities, thus, the ongoing search for natural antimicrobials for prevention of food-borne illnesses is a vast exploring area for scientists. Antimicrobial activities of pomegranate have been studied by some researchers and the extent of inhibitory effect is always attributed to the pomegranate antioxidant activity that depends mainly on the phenolic and anthocyanin content of the fruit (Holetz et al, 2002;Braga et al, 2005;Mathabe et al, 2006;McCarrell et al, 2008;Al-Zoreky, 2009;Duman et al, 2009;Gould et al, 2009;Parashar et al, 2009;Panichayupakaranant et al, 2010, Orak et al, 2011. In a previous study, Opara et al (2009) reported that the best activity against Staphyloccocus aureus and Pseudomonas aeruginosa were found in fruit peel compound punicalagin, particularly from Oman, which was coincident with the highest levels of vitamin C detected in these samples.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%